Legal Analysis in Mitigating Environmental Impacts Due to Coal Mining in Batanghari Regency, Jambi Province - Ternando, Albi (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Jambi Province is one of the provinces in Indonesia with natural mining wealth which contains many natural resource reserves. The processing of these natural resources has the potential to be managed as an energy source very well, such as the natural resources contained in it are coal. one of the areas in Kotoboyo village, Dalam subdistrict XXIV, Batanghari Regency, Jambi Province, is one of the largest coal producing areas in Indonesia, this area has been very productive in recent years, several coal mining companies have been located in the area, this does not necessarily mean that This means that the results of coal reserves can have a positive impact on the people who live in the surrounding area. In fact, there tends to be no visible environmental impact on the community. The mining activity process around the mine still uses national public road access, causing traffic jams that last for kilometers and disrupt traffic. crossing public roads in local communities, the Central, Regional Government and the Ministry of Energy and Mineral Resources should firmly work together to face the polemics that occur in the community as quickly as possible to provide solutions so that special road access to reduce the massive mobility of coal mining movements can be realized immediately for the prosperity of the community's economic movement.